KSU W.I.N.D.: Kansas State University WFS information networking & display - Kubler, Sarah Marie; Cowley, Shawn; Youssef, Mina (Kansas State University, 2009)
The presentation will explain a current research project that is being performed by students in the ECE department at KSU. The research project is to create a database and a website. The information being stored and displayed is the data from wind turbines that are being put up for the Wind for Schools program. The project faces a technical challenge in developing a reliable multi-network system. A computer at KSU will be used to access the computer at the different sites to collect the individual turbine data. The data will be used in developing a virtual distributed-source renewable energy power system, to study efficient ways to incorporate small wind and solar energy generators into the electric grid without the loss of reliability. The information will also be able to be used in classrooms across Kansas to teach students about Wind Energy. The website will allow students to compare the power generation at different locations and to download raw data files for use in research. This will allow children in Kansas to learn about wind energy at a young age. The researchers are currently collaborating with other universities to make this a national webpage with data from all the states that participate in Wind for Schools. With the help of other universities the researchers will be able to create one website that schools across the country can use when teaching about wind energy. This work is supported in part by grants from DOE/NREL Wind Powering America and the KSU Center for Sustainable Energy.
Keywords: Sustainable energy; Wind turbines; Wind for Schools; Children